Injectable composites of loose microfibers and gelatin with improved interfacial interaction for soft tissue engineering. (15th September 2015) - Poveda-Reyes, Sara; Rodrigo-Navarro, Aleixandre; Gamboa-Martínez, Tatiana C.; Rodíguez-Cabello, José C.; Quintanilla-Sierra, Luis; Edlund, Ulrica; Ferrer, Gloria Gallego
Abstract: Poly(l -lactic acid) (PLLA) microfibers were surface functionalized by graft photopolymerization of 2-hydroxyethyl methacrylate (HEMA) onto the fiber surface. Grafted fibers were easily dispersed in enzymatically gelling tyramine-substituted gelatin, forming a homogeneous dispersion without hindering subsequent gelatin crosslinking. The obtained injectable hydrogels showed improved mechanical properties compared to analogues based on non-modified fibers. The composite with 1% (w/v) of surface modified fibers had a three-fold higher shear storage modulus (535.2 ± 90 Pa) than pure gelatin (184.9 ± 32 Pa) while no significant increase was observed in the case of non-grafted fiber composites. Moreover, PHEMA grafting on PLLA fibers did not compromise cell viability and proliferation within the hydrogel. The new injectable hydrogels offer improved potential as substrates for the regeneration of soft tissues. Graphical abstract: Highlights: Loose PLLA microfibers were successfully manufactured. PHEMA grafting onto PLLA microfibers improved their hydrophilicity. Grafted fibers were easily dispersed in the gelatin solution to produce injectable PLLA/gelatin composites. The mechanical properties of the composites increased proportionally to the quantity of PHEMA-grafted fibers. The fibers do not compromise hydrogel injectability, cell encapsulation and cell proliferation.